Bernardo Élis em sala de aula da EJA : sequências didáticas para letramento literário - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
In the area of literature teaching, this work reflects on literary literacy in Educação de Jovens e Adultos - EJA, based on the fictional writing by Bernardo Élis. This writer from Goiás reveals the landscapes, customs, traditions, and dilemmas faced by the inhabitants of the backcountry. The author’s style allows us to recognize an important connection between literature and EJA, considering that the audience of this educational modality was not granted the right to education at the appropriate age nor the right to art and literature. Thus, we propose didactic sequences for classroom reading of the following short stories: “O caso inexplicável da orelha Lolô”, “Os fuxicos da fonte do Taquari” and “A enxada”, all of which share common characters subjected to adverse conditions. The research is qualitative and bibliographic, based on theorists such as Antonio Candido (1972a, 1989, 2000, 2004, 2006); Paulo Freire (1969, 1989, 1991, 1996, 2005, 2006, 2011); Miguel Arroyo (2000, 2005, 2011) and Rildo Cosson (2014, 2021a, 2021b), among others. In the first chapter, we present a historical overview of EJA, addressing importance of Paulo Freire for this educational modality; in the second chapter, we discuss the short story genre, its approach in the classroom, the teaching of literature, literary literacy, and the characteristics of style of Élis; and, in the third chapter, we analyze the selected short stories and propose didactic sequences to work them in the classroom. At the end of this research, we intend to offer a contribution to the literary literacy of EJA classes and, at the same time, reaffirm the literary merit of short stories by Élis in awakening critical awareness among readers, which is essential for liberating education
Bernardo Élis in the EJA classroom : didactic sequences for literary literacy
Keywords: EJA; Letramento literário; Conto; Bernardo Élis; Literary literacy; Short story; LINGUISTICA, LETRAS E ARTES; LETRAS::LITERATURA BRASILEIRA